Sistem Informasi Monitoring Pembangunan Perekonomian Berbasis Mobile di Kabupaten Bondowoso - Herlinatus Safira Muasolli; Akhlis Munazilin (LP2M Universitas Ibrahimy, 2025)
Development Monitoring in Bondowoso Regency requires an effective and efficient monitoring system. A mobile-based information system can be a solution to improve transparency, accuracy, and speed of access to development data. This study aims to design and build a mobile-based economic development monitoring information system in Bondowoso Regency. The system development method used is SDLC. This system will integrate data from various development monitoring sectors and display it in the form of an interactive dashboard that is easily accessible by the General and Planning Department, apparatus, and section heads. It is expected that this system can help make better decisions and encourage public participation in regional economic development.